2011
DOI: 10.1029/2010jd014462
|View full text |Cite
|
Sign up to set email alerts
|

Global electric circuit implications of combined aircraft storm electric current measurements and satellite-based diurnal lightning statistics

Abstract: [1] We have combined analyses of high-altitude aircraft observations of electrified clouds with diurnal lightning statistics from the Lightning Imaging Sensor (LIS) and Optical Transient Detector (OTD) that are carried aboard low-Earth-orbiting satellites to reproduce the diurnal variation in the global electric circuit. Using basic assumptions about the mean storm currents as a function of flash rate and location (i.e., land or ocean) and the global electric circuit, our estimate of the current in the global … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
152
2
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(169 citation statements)
references
References 26 publications
13
152
2
2
Order By: Relevance
“…This led to an estimate that thunderstorms contribute 90%, and electrified clouds contribute 10% to current flow in the GEC. Mach et al (2011) also observed large differences between land and ocean storms, with land storms generating greater lightning rates, but smaller mean conduction currents than ocean storms. Thus most of the observed amplitude variation of the Carnegie curve can be accounted for by correctly including the differences that exist in the mean currents and flash rates between land and ocean thunderstorms.…”
Section: Current Flow Above Thunderstormsmentioning
confidence: 97%
See 3 more Smart Citations
“…This led to an estimate that thunderstorms contribute 90%, and electrified clouds contribute 10% to current flow in the GEC. Mach et al (2011) also observed large differences between land and ocean storms, with land storms generating greater lightning rates, but smaller mean conduction currents than ocean storms. Thus most of the observed amplitude variation of the Carnegie curve can be accounted for by correctly including the differences that exist in the mean currents and flash rates between land and ocean thunderstorms.…”
Section: Current Flow Above Thunderstormsmentioning
confidence: 97%
“…Mach et al (2011) concluded that the mean total conduction current is 2.0 kA, where contributions to the GEC from land and ocean thunderstorms are 1.1 kA and 0.7 kA, respectively, and electrified shower clouds contribute 0.04 kA and 0.22 kA for land and ocean storms, respectively. Measurements such as these are essential to our understanding of the GEC and will aid in the development of future GEC models.…”
Section: Summary Of Measurements In Thunderstormsmentioning
confidence: 99%
See 2 more Smart Citations
“…He even deployed his childhood microscope for thunderstorm electricity measurements (Wilson, 1960). Evidence of the success of the Wilson apparatus lies in its longevity, as it was used in an almost identical manner until 1979 at Kew Observatory, having been moved to an underground laboratory in 1931 (Harrison and Ingram, 2005). Beyond its original scientific application, data from the Wilson apparatus has proved suitable for reconstructing historic air pollution data (Harrison, 2006).…”
Section: Remember the Satisfaction I Had When My Work Led To The Fumentioning
confidence: 99%